2016
DOI: 10.1016/j.paid.2016.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Belief in divine moral authority: Validation of a shortened scale with implications for social attitudes and moral cognition

Abstract: Highlights: A shortened, 5-item scale measuring belief in divine moral command is established  The scale shows good construct, convergent, and incremental validity  Divine Command beliefs best explain religious believers' attitudes toward atheists  Also best explain believers' propensity toward deontological/prohibitive morality  This scale should be important in ongoing research into religious/moral psychology BELIEF IN DIVINE MORAL AUTHORITY 3 ABSTRACT Religion and morality have been deeply interwoven t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…For instance, exposure to war (Haskuka, Sunar, & Alp, 2008) or abusive/dysfunctional family relations (Caselles & Milner, 2000) impedes moral reasoning. More generally, many studies have shown that the moral judgments people make depend on their age, gender (e.g., Kray & Haselhuhn, 2012; Skoe, Cumberland, Eisenberg, Hansen, & Perry, 2002), parental status, education, multicultural experiences (Lin, 2009), war experiences, family experiences, or religious status (Simpson, Piazza, & Rios, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, exposure to war (Haskuka, Sunar, & Alp, 2008) or abusive/dysfunctional family relations (Caselles & Milner, 2000) impedes moral reasoning. More generally, many studies have shown that the moral judgments people make depend on their age, gender (e.g., Kray & Haselhuhn, 2012; Skoe, Cumberland, Eisenberg, Hansen, & Perry, 2002), parental status, education, multicultural experiences (Lin, 2009), war experiences, family experiences, or religious status (Simpson, Piazza, & Rios, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The Morality Founded on Divine Authority scale (MFDA; Simpson, Piazza, & Rios, 2016) was developed to assess the meta-ethical belief that moral rules are issued by God. The 5-item scale (which uses a Likert-type format) includes questions such as “What is morally good and right is what God says is good and right.” Simpson et al (2016) reported an internal consistency estimate of .94.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, these foundations reveal the sharpest distinction between religious and secular/atheistic moral values. Moreover, some evidence suggests that believers' own endorsements of the Binding foundations (especially Sanctity) predict anti‐atheist prejudice more strongly than endorsements of the Individualizing foundations (e.g., Graham et al, ; Simpson, Piazza, & Rios, ). Together, such research suggests that atheists will be judged more favorably if they are perceived to endorse the Binding foundations (particularly Sanctity), thus redressing their relative disregard for values important in religious moral systems.…”
Section: Moral Foundations and Anti‐atheist Prejudicementioning
confidence: 99%